Caracterização morfodinâmica e sedimentologia da Plataforma Continental Rasa na APA Estadual dos Recifes de Corais - RN - Santos, Jonas Ricardo dos (2010)
This study had to aimed to characterize the sediments of shallow continental shelf and realize the mapping of features visible for satellite images by using remote sensing techniques, digital image processing and analysis of bathymetry between Maxaranguape and Touros - RN. The study s area is located in the continental shallow shelf of Rio Grande do Norte, Brazil, and is part of the Environmental Protection Area (APA) of Coral Reefs. A total of 1186 sediment samples were collected using a dredge type van veen and positioning of the vessel was made out with the aid of a Garmin 520s. The samples were treated In the laboratory to analyze particle size of the sediment, concentration of calcium carbonate and biogenic composition. The digital images from the Landsat-5 TM were used to mapping of features. This stage was used the band 1 (0,45-1,52 μm) where the image were georeferenced, and then adjusting the histogram, giving a better view of feature bottom and contacts between different types of bottom. The results obtained from analysis of the sediment showed that the sediments of the continental shelf east of RN have a dominance of carbonate facies and a sand-gravelly bottom because the region is dominated by biogenic sediments, that are made mainly of calcareous algae. The bedform types identified and morphological features found were validated by bathymetric data and sediment samples examined. From the results obtained a division for the shelf under study is suggested, these regions being subdivided, in well characterized: (1) Turbid Zone, (2) Coral Patch Reefs Zone, (3) Mixed Sediments Carbonates Zone, ( 4) Algae Fouling Zone, (5) Alignment Rocky Zone, (6) Sand Waves Field (7) Deposit siliciclastic sands